1979
DOI: 10.1159/000232296
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Microsomal Antigen and Its Antibody in Human Liver Diseases

Abstract: Sera of 173 patients with various forms of liver disease along with serum precipitates produced by polyethylene glycol were screened for the presence of a microsomal antigen referred to as ubiquitous tissue antigen (UTA) and its antibody by double diffusion precipitation in agarose gel. UTA was detected in 7 of 26 patients with chronic active hepatitis, 1 of 5 with alcoholic hepatitis, 2 of 14 with alcoholic cirrhosis and 18 of 98 with hepatoma. Antibodies to UTA were found only in 2 patients with chronic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…These results essentially confirmed those reported in previous studies includ ing the initial studies of UTA [1,2,4,6]. In the present study, antidextran antibodies were found in 22% and the dextran antigen in 15% of the patients with liver diseases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results essentially confirmed those reported in previous studies includ ing the initial studies of UTA [1,2,4,6]. In the present study, antidextran antibodies were found in 22% and the dextran antigen in 15% of the patients with liver diseases.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, all patients with high levels of the anti gen in their sera showed a definite elevation of serum transaminases indicating destruction of hepatic cells. In this respect, as it has been suggested by other inves tigators [3,6], the appearance of the dextran antigen in the patients' circulation may be considered an indi cator of the disease activity.…”
Section: Discussionmentioning
confidence: 79%